Simulation test of disc brake functionality using computer aided engineering software - Abdul Faizal, Abd Halim (2008)
This thesis deals with simulation test of disc brake functionality by using computer aided engineering software. The objective of this thesis is to investigate and analyze the stress distribution of disc brake during operation using CAE software. The thesis describes the finite element analysis techniques to predict the failure region on the brake disc and to identify the critical locations of the components. The disc brake implemented on the front axle of Proton Wira 1998 model with gray cast iron materials were studied in this thesis which commonly used in industry. Despite all the stresses experience by the disc doesn’t damage the disc due to high tensile strength but the disc may fail under fatigue loading. It is important to determine the critical area of concentrated stress, so appropriate modification can be made. The structural three-dimensional solid modelling of brake disc was developed using the computer-aided drawing software. The strategy of validation of finite element model was developed. The finite element analysis was then performed using ALGOR-Fempro. The finite element model of the components was analyzed using the static stress with linear material model approaches. Finally, the stress distribution obtain from the result of analysis are employed as input for the failure region. From the results, it is observed that the analysis using Fempro can predict the failure region under fatigue loading. The acquired results tell the failure region occurred at the outer radius for both side of the brake disc due to concentrated maximum stress in these regions. Concentrated stress at these regions may promote conning effect. By moving the contact area of the brake pads and brake disc inside and away from the edge, maximum stress at the outer radius of the disc can be reduced or prevented. The stress analysis results are significant to improve the component design at the early developing stage. The results can also significantly reduce the cost and time to market, and improve product reliability and customer confidence.